2022
DOI: 10.1039/d1cp04729a
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structures of hydroxylated low index surfaces of rutile and anatase-type titanium dioxide

Abstract: Different surface planes of various types of TiO2 crystals have diverse catalysis effects on the splitting of H2O and H2 and the electronic structures of the formed hydroxylated titanium dioxide...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 53 publications
(87 reference statements)
5
17
0
4
Order By: Relevance
“…The 101 surface of anatase-TiO 2 , 110 surface of rutile-TiO 2 , and 210 surface of brookite-TiO 2 were chosen, being denoted as A-101, R-110, and B-210, respectively. Similar to that in our earlier investigations, 31 the surface hydroxyl group generated by the splitting of water on a pure surface was labeled OH1 while the surface hydroxyl group generated by the splitting of H 2 O on an oxygen-deficient surface or H 2 on a pure surface was labeled OH2. As reported by Valdes et al , 28 there are two distinct types of O* intermediates on the TiO 2 surface for the OER process: one is an O atom that is hanging on the surface (designated as O d *), and the other is a structure with the chemical formula Ti–O–O–Ti that reacts with surface oxygen to generate peroxide (designated as O p *).…”
Section: Computation Methodologysupporting
confidence: 76%
See 2 more Smart Citations
“…The 101 surface of anatase-TiO 2 , 110 surface of rutile-TiO 2 , and 210 surface of brookite-TiO 2 were chosen, being denoted as A-101, R-110, and B-210, respectively. Similar to that in our earlier investigations, 31 the surface hydroxyl group generated by the splitting of water on a pure surface was labeled OH1 while the surface hydroxyl group generated by the splitting of H 2 O on an oxygen-deficient surface or H 2 on a pure surface was labeled OH2. As reported by Valdes et al , 28 there are two distinct types of O* intermediates on the TiO 2 surface for the OER process: one is an O atom that is hanging on the surface (designated as O d *), and the other is a structure with the chemical formula Ti–O–O–Ti that reacts with surface oxygen to generate peroxide (designated as O p *).…”
Section: Computation Methodologysupporting
confidence: 76%
“…In accordance with our earlier research, 31 the A-101, R-110, and B-210 surfaces were each modified with hydroxyl groups of the OH1 and OH2 types. Fig.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…18 A recent article that calculated the electronic structures of hydroxylated low-index surfaces of rutile and anatase titanium dioxide, suggested that hydroxyl-bridged surfaces have a lot of potential for photo-electrocatalysis but did not directly assess the catalytic performance of these lowindex facets. 62 In the absence of studies identifying the role of each crystal facet in photocatalytic redox reactions, the understanding of photo-oxidation of water by nano-titania is incomplete as only 64% of particle surfaces are (110). [63][64][65] Thus, computational studies that can separately calculate the properties of each surface are critical to understanding the reactivity of experimental nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, the dissociation of species on surfaces in a water environment are adsorbed oxygen species like hydroxyl-bridges. 62 Before computational effort is invested in fully exploring the reactivity of other low-index surfaces of rutile TiO 2 , a detailed understanding of the complex oxidation of water on each stoichiometric surface is required.…”
Section: Introductionmentioning
confidence: 99%